Pyrrolo[3,2-c]pyridine derivatives with potential inhibitory effect against FMS kinase: in vitro biological studies - Mohammed I. El-Gamal; Chang-Hyun Oh (Taylor & Francis Group, 2018)
A series of eighteen pyrrolo[3,2-c]pyridine derivatives were tested for inhibitory effect against FMS kinase. Compounds 1e and 1r were the most potent among all the other tested analogues (IC50 = 60 nM and 30 nM, respectively). They were 1.6 and 3.2 times, respectively, more potent than our lead compound, KIST101029 (IC50 = 96 nM). Compound 1r was tested over a panel of 40 kinases including FMS, and exerted selectivity against FMS kinase. It was further tested against bone marrow-derived macrophages (BMDM) and its IC50 was 84 nM (2.32-fold more potent than KIST101029 (IC50 = 195 nM)). Compound 1r was also tested for antiproliferative activity against a panel of six ovarian, two prostate, and five breast cancer cell lines, and its IC50 values ranged from 0.15-1.78 µM. It possesses also the merit of selectivity towards cancer cells than normal fibroblasts.